2002
DOI: 10.1016/s0967-0645(02)00329-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton growth, microzooplankton herbivory and community structure in the southeast Bering Sea: insight into the formation and temporal persistence of an Emiliania huxleyi bloom

Abstract: Using the seawater dilution technique, we measured phytoplankton growth and microzooplankton grazing rates within and outside of the 1999 Bering Sea coccolithophorid bloom. We found that reduced microzooplankton grazing mortality is a key component in the formation and temporal persistence of the Emiliania huxleyi bloom that continues to proliferate in the southeast Bering Sea. Total chlorophyll a (Chl a) at the study sites ranged from 0.40 to 4.45 mg C l À1 . Highest phytoplankton biomass was found within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 69 publications
4
108
2
Order By: Relevance
“…However, it was recently suggested that DMSP rather than acrylate is the active deterrent of microzooplankton grazing (Strom et al 2003b) and readers are directed to the paper presented by Nejstgard et al (this issue) for a discussion on this subject. A few field experiments have combined the determination of microzooplankton grazing rates (the Landry-Hassett dilution technique) with DMS(P) analyses and have shown that DMSP-containing algal species may be proportionally less grazed than total algal biomass (Archer et al 2001b;Olson and Strom 2002;Wolfe et al 2000). However, several problems are associated with this technique and we refer to Archer et al (2001b) for a discussion on the potential pitfalls.…”
Section: Grazing By Microzooplanktonmentioning
confidence: 99%
“…However, it was recently suggested that DMSP rather than acrylate is the active deterrent of microzooplankton grazing (Strom et al 2003b) and readers are directed to the paper presented by Nejstgard et al (this issue) for a discussion on this subject. A few field experiments have combined the determination of microzooplankton grazing rates (the Landry-Hassett dilution technique) with DMS(P) analyses and have shown that DMSP-containing algal species may be proportionally less grazed than total algal biomass (Archer et al 2001b;Olson and Strom 2002;Wolfe et al 2000). However, several problems are associated with this technique and we refer to Archer et al (2001b) for a discussion on the potential pitfalls.…”
Section: Grazing By Microzooplanktonmentioning
confidence: 99%
“…and Protoperidinium spp. are known to prey on diatoms and, thus, strongly regulate the phytoplankton community (Olson and Strom, 2002). Therefore, these increases in microzooplankton and the decrease in diatoms may be caused by microzooplankton grazing on diatoms.…”
Section: Short-term Changes In the Microplankton Communitymentioning
confidence: 99%
“…In the marine ecosystem of the western Arctic Ocean, microplankton, including diatoms, dinoflagellates and ciliates, play several roles, such as primary producers, consumers and food resources for mesozooplankton Sherr, 1988, Sherr et al, 1997;Olson and Strom, 2002). The microplankton community in the western Arctic Ocean is divided into three groups -shelf, continental slope and basin (Sukhanova et al, 2009;Matsuno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…If micronutrients were scarce, the relatively low iron and zinc requirements of E. huxleyi (reviewed in Paasche 2002) may have been a factor in its success. It is interesting to note as well that E. huxleyi was preferentially grazed in the North Atlantic bloom , whereas data (Olson and Strom 2002) and modeling ) of the coastal Bering Sea bloom indicated that reduced grazing was important in bloom initiation and duration. It may well be that factors that govern the dynamics of oceanic blooms of E. huxleyi are different from those of coastal blooms.…”
mentioning
confidence: 99%